2015
DOI: 10.1177/1542305015602708
|View full text |Cite
|
Sign up to set email alerts
|

On Strengthening Compassionate Care for Muslim Patients

Abstract: In this piece, I contribute to an ongoing conversation on compassionate care for Muslim patients. I address the various barriers hindering such care and ways in which to work around them. In providing an introductory understanding of general Islamic beliefs on the definition of life, the use of palliative care, etc., I hope this reflection can offer insight into the general background of Muslim patients and spark interest in further reading and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Zaidi showed that when the nurse and patient have the same gender, the nurse is more motivated to talk about the patient's personal matters. [26] In a study, gender difference between patients and nurses was considered an important cultural barrier to effective communication. [27] Cultural and religious differences between Islamic and Western countries could explain these differences, because some compassionate behaviors such as touching the hands of the opposite sex are improper according to Islam, and to expand compassionate behaviors, Muslim nurses must work based on Islamic rules.…”
Section: Discussionmentioning
confidence: 99%
“…Zaidi showed that when the nurse and patient have the same gender, the nurse is more motivated to talk about the patient's personal matters. [26] In a study, gender difference between patients and nurses was considered an important cultural barrier to effective communication. [27] Cultural and religious differences between Islamic and Western countries could explain these differences, because some compassionate behaviors such as touching the hands of the opposite sex are improper according to Islam, and to expand compassionate behaviors, Muslim nurses must work based on Islamic rules.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of how Muslim family members use their religion could equip hospital staff members and administrators to understand and support these religious practices. This perspective mirrors the comments of a Muslim chaplain that “a grounded understanding of general Islamic beliefs on the definition of life, the use of palliative care, etc … offers caregivers the potential to greatly improve patient experience and satisfaction” (Zaidi, 2015, p. 173). Supporting Muslim religious beliefs in the context of hospitalization is not only a sign of respect but, based on results from this study, is key to assisting Muslim families in their medical decision-making.…”
Section: Resultsmentioning
confidence: 54%
“…Some programs may offer formal training on the intersection of health care and Islam, but access is limited to certain professions such as physician trainees. 47 46,48 With the growing focus on interprofessional health professions education and interdisciplinary health care delivery, 49 it may be beneficial to add a Muslim clinician to the health care team in areas where there are substantial Muslim populations. Similarly, Muslim chaplains should be made available in health care facilities, working collaboratively with local imams and facility staff to respond to patients' needs.…”
Section: Discussionmentioning
confidence: 99%
“…24 Obtaining informed consent before the administration of pain medication, although not a standard process in most US hospitals, documents the choice made. 46…”
Section: Pain Managementmentioning
confidence: 99%